A study on Silverstone Berhad's collective bargaining process "Analysis of 2011 and 2014 Collective Agreements on terms and conditions of employment" / Lutfia Hannah Abdul Malik - Abdul Malik, Lutfia Hannah (2016)
This research is to examine the Silverstone Berhad’s Collective Bargaining procedures, to examine the Union’s proposal for the 8th Collective Agreement whether it taken into consideration by the employer into a Collective Agreement; to diagnose the changes in the CA for the year 2011 and 2014 and to determine the level of conformance and non conformance of CA terms and conditions of employment in accordance to the Malaysian Employment Laws. The data and information are obtained from the Collective Agreement of 2011 and 2014 and also from the person in charge directly with the Collective Bargaining procedures. Based from this research, it shows that the Silverstone Berhad’s are complied with the Malaysian Employment Laws, in addition, the company offer better benefits to their workers as compared the basic guidelines in the Employment Act 1955. Besides that, the Collective Bargaining process takes less than a year to conclude and it is shown a harmonious relationships between both parties.